Active Ingredients and Potential Mechanism of Additive Sishen Decoction in Treating Rheumatoid Arthritis with Network Pharmacology and Molecular Dynamics Simulation and Experimental Verification - Ren J; Liu Z; Qi X; Meng X; Guo L; Yu Y; Dong T; Li Q (Drug Design, Development and Therapy)
Jinhong Ren, Ze Liu, Xiaoming Qi, Xiangda Meng, Linglin Guo, Yating Yu, Tao Dong, Qingshan Li Shanxi Key Laboratory of Innovative Drug for the Treatment of Serious Diseases Basing on the Chronic Inflammation, College of Traditional Chinese Medicine and Food Engineering, Shanxi University of Chinese Medicine, Jinzhong, People’s Republic of ChinaCorrespondence: Qingshan Li, Email sxlqs0501@sxtcm.edu.cnBackground: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease in which macrophages produce cytokines that enhance inflammation and contribute to the destruction of cartilage and bone. Additive Sishen decoction (ASSD) is a widely used traditional Chinese medicine for the treatment of RA; however, its active ingredients and the mechanism of its therapeutic effects remain unclear.Methods: To predict the ingredients and key targets of ASSD, we constructed “drug-ingredient-target-disease” and protein–protein interaction networks. Gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed to explore the potential mechanism. The activity of the predicted key ingredients was verified in lipopolysaccharide-stimulated macrophages. The binding mode between the key ingredients and key targets was elucidated using molecular docking and molecular dynamics simulation.Results: In all, 75 ASSD active ingredients and 1258 RA targets were analyzed, of which kaempferol, luteolin, and quercetin were considered key components that mainly act through inflammation-related pathways, such as the PI3K-AKT, TNF, and IL-17 signaling pathways, to ameliorate RA. Transcriptome sequencing suggested that kaempferol-, luteolin-, and quercetin-mediated inhibition of glycolysis reduced the lipopolysaccharide-induced production of proinflammatory factors. In vitro experiments indicated that kaempferol, luteolin, and quercetin decreased Glut1 and LDHA expression by diminishing PI3K-AKT signaling to inhibit glycolysis. Molecular dynamic simulation revealed that kaempferol, luteolin, and quercetin stably occupied the hydrophobic pocket of PI3Kδ.Conclusion: Our results show that the PI3Kδ-mediated anti-inflammatory responses elicited by kaempferol, luteolin, and quercetin are crucial for the therapeutic efficacy of ASSD against RA.Keywords: Autoimmune disease, traditional Chinese medicine, glycolysis, inflammation, PI3K-AKT